Philosophical Issues in the Legislation of Islam: Right, Women, and Money - Abdulaziz Omar A. Jughaiman (European Scientific Journal, ESJ, 2019)
This paper focuses on exploring a contemporary issues in the Islamic legislations as a religion from a scientific and philosophical perspective, approach of Islam with science, and major goals of Islam in terms of rights, money, and woman. It also aims to explore the phenomenon, true concepts, and the concepts of this ideology. Based on these definitions and formulas, a two survey study was designed and used from two stage stratified random sample of cluster. The final sampling units were selected randomly from the primary sampling units (25 families from every count regions) using a systematic random sample. In this present study, it was found that for a chosen country, the Polygamy percentage is about 0.1% of married female. Only 2.11% out of the total employed female renders supports to their family. Unmarried females who are 15 years old and over with Pregnancy are less by 24.1% when compared to unmarried males. There is a high dependence on men in the case of family supporting. In conclusion, successful application of Islam with science depends on the possibility of applying them together. Therefore, the explanations and definitions of many important legislation, phenomenon, and concepts, in addition to some formulas, were suggested. This, however, would have a significant contribution to a better understanding of many phenomena in the religion, ethic, law, economic, society, and politics.